2012
DOI: 10.1158/1541-7786.mcr-11-0287
|View full text |Cite
|
Sign up to set email alerts
|

The E6 Oncoprotein from HPV16 Enhances the Canonical Wnt/β-Catenin Pathway in Skin Epidermis In Vivo

Abstract: The contribution of the Wnt signaling pathway to HPV-induced carcinogenesis is poorly understood. In high-grade dysplastic lesions that are caused by high-risk human papilloma viruses (HR-HPVs), β-catenin is often located in the cell nucleus, which suggests that Wnt pathway may be involved in the development of HPV-related carcinomas. Most of the oncogenic potential of HR-HPVs resides on the E6 protein’s PDZ-binding domain. We hypothesized that the PDZ-binding domain of the HPV16-E6 oncoprotein induces the nuc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 36 publications
(53 reference statements)
0
43
0
Order By: Relevance
“…It was also proposed that activation of canonical WNT signaling could be induced in vivo by the HPV16-E6 oncoprotein [46]. In our study, it remains to be elucidated whether HPV oncoproteins are involved in WNT7A downregulation, the goal toward which we are currently working.…”
Section: Discussionmentioning
confidence: 86%
“…It was also proposed that activation of canonical WNT signaling could be induced in vivo by the HPV16-E6 oncoprotein [46]. In our study, it remains to be elucidated whether HPV oncoproteins are involved in WNT7A downregulation, the goal toward which we are currently working.…”
Section: Discussionmentioning
confidence: 86%
“…Our observations are consistent with those of Wilding et al , who found that co-transfection of an immortalized keratinocyte cell line with HPV-16 E6 and E7 led to redistribution of α-, β-, and γ-catenins from the undercoat membrane to the cytoplasm 28 . Furthermore, in transgenic mice, HPV16 E6 oncoprotein enhanced the nuclear accumulation of β-catenin 29 . A study from Rampias et al .…”
Section: Discussionmentioning
confidence: 96%
“…Although outside the scope of this study, observations in the literature suggest a likely candidate to be the Wnt pathway. Previous reports have shown that the E6 protein can activate the Wnt pathway in the epidermis of transgenic mouse expressing full-length E6 oncoprotein [24], and in HPV16-positive oropharyngeal squamous carcinoma cells [25]. The activation of the Wnt signalling pathway and of mTOR signalling has also been observed in tumour samples from the E6 variants non-European cervical cancer patients [26].…”
Section: Discussionmentioning
confidence: 96%